Involvement of Multiple Loci in Quorum Quenching of Autoinducer I Molecules in the Nitrogen-Fixing Symbiont Rhizobium (Sinorhizobium) sp. Strain NGR234 - Krysciak, D. (American Society for Microbiology, 2011)
Rhizobium sp. strain NGR234 is a unique alphaproteobacterium (order Rhizobiales) that forms nitrogen-fixing nodules with more legumes than any other microsymbiont. Since we have previously described the complete genome sequence of NGR234, we now report on a genome-wide functional analysis of the genes and enzymes involved in autoinducer I hydrolysis in this microbe. Altogether we identified five cosmid clones that repeatedly gave a positive result in our function-based approach for the detection of autoinducer I hydrolase genes. Of these five cosmid clones, two were located on pNGR234b and three were on cNGR234. Subcloning and in vitro mutagenesis in combination with BLAST analyses identified the corresponding open reading frames (ORFs) of all cosmid clones: dlhR, qsdR1, qsdR2, aldR, and hitR-hydR. Analyses of recombinant DlhR and QsdR1 proteins by using high-performance liquid chromatography-mass spectrometry (HPLC-MS) demonstrate that these enzymes function as acyl homoserine lactone (AHL) lactonases. Furthermore, we showed that these enzymes inhibited biofilm formation and other quorum-sensing-dependent processes in Pseudomonas aeruginosa, Chromobacterium violaceum, and Agrobacterium tumefaciens. Finally, our experimental data suggest that competitive colonization of roots in the rhizospheres of cowpea plants is affected by DlhR and QsdR1.